Conservation and Diversity of miR166 Family Members From Highbush Blueberry (Vaccinium corymbosum) and Their Potential Functions in Abiotic Stress - Li, Yuening; Wang, Xianglong; Guo, Qingxun; Zhang, Xinsheng; Zhou, Lianxia; Zhang, Yang; Zhang, Chunyu (Frontiers in Genetics, 2022)
MicroRNA166 (miR166) is highly conserved and has diverse functions across plant species. The highbush blueberry (Vaccinium corymbosum) genome is thought to harbor 10 miRNA166 loci (Vco-miR166), but the extent of their evolutionary conservation or functional diversification remains unknown. In this study, we identified six additional Vco-miR166 loci based on conserved features of the miR166 family. Phylogenetic analyses showed that mature Vco-miR166s and their precursor cluster in several clades are evolutionary conserved with diverse species. The cis-regulatory elements in the Vco-miR166 promoters indicated functions related to different phytohormones and defense responses. We also identified putative targets of vco-miR166s, which targeted the same gene families, suggesting the functional conservation and diversification of Vco-miR166 family members. Furthermore, we examined the accumulation patterns of six mature Vco-miR166s in response to abiotic stresses by stem-loop reverse RT-qPCR, which revealed their upregulation under freezing, cold, and heat stress, while they were downregulated by drought compared to control growth conditions. However, Vco-miR166 members showed different expression patterns when exposed to salt stress. These results showed that conserved Vco-miR166 family members display functional diversification but also coordinately influence plant responses to abiotic stress.